Unveiling the Concordance: Pirani Score and Key Radiological Angles (TCA AP, Talo-1st Metatarsal) in Monitoring Ponseti-Treated Congenital Talipes Equinovarus - Muhammad Randi Akbar; Mochamad Ridho Nur Hidayah; Debby Handayati Harahap (Sriwijaya Journal of Surgery, 2025)
Introduction: Congenital talipes equinovarus (CTEV) is a significant pediatric foot deformity. The Ponseti method, assessed clinically by the Pirani score, is the standard treatment. However, the precise relationship between this clinical score and objective radiological measurements, particularly key angles like the talocalcaneal anteroposterior (TCA AP) and talo-first metatarsal (Talo-1st MT) angles, requires ongoing detailed investigation to optimize treatment monitoring. This study aimed to meticulously evaluate the correlation between Pirani scores and these specific radiological parameters in CTEV patients undergoing Ponseti management at a tertiary care center in Palembang, Indonesia. Methods: A descriptive case series was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, involving 29 infants with idiopathic CTEV. Clinical assessments using the Pirani score and radiological evaluations measuring TCA AP, Talo-1st MT, lateral talocalcaneal (TCA lateral), and lateral tibiocalcaneal (TiCA lateral) angles were performed before initiating and after completing the Ponseti casting phase. Spearman’s rank correlation coefficient was utilized to analyze the relationship between Pirani scores and these radiological angles. Results: Significant improvements were observed in both Pirani scores (mean pre-treatment 4.36 ± 1.41 to post-treatment 0.20 ± 0.29; p < 0.001) and radiological parameters following Ponseti treatment. Pre-correction, Pirani scores showed very strong positive correlations with TCA AP (r = 0.892, p < 0.001), Talo-1st MT (r = 0.939, p < 0.001), and TCA lateral (r = 0.880, p < 0.001). Post-correction, moderate significant positive correlations persisted for TCA AP (r = 0.404, p = 0.045) and Talo-1st MT (r = 0.404, p = 0.045) with Pirani scores. The TiCA lateral angle showed weaker and less consistent correlations. Conclusion: Key radiological parameters, specifically the TCA AP and Talo-1st MT angles, demonstrate a significant correlation with the Pirani score both before and after Ponseti correction in CTEV patients. These findings underscore the synergistic value of integrating these specific radiological assessments with clinical Pirani scoring for comprehensive monitoring of deformity correction during Ponseti treatment.